2018
DOI: 10.1016/j.jadohealth.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Age for Screening Adolescents and Young Adults Without Identified Risk Factors for HIV

Abstract: For U.S. AYA without identified risk factors, a one-time routine HIV screen at age 25, after the peak of incidence, would optimize clinical outcomes and be cost-effective compared with current U.S. screening practices. Focusing screening on AYA ages 18 or younger is a less efficient use of a one-time screen among AYA than screening at a later age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Despite having lower levels of HIV knowledge, women's HIV testing rates are much higher than for men, at 62% versus 27%. This seems to be a constant finding across studies (9)(10)(11)20). It suggests that women have better access to health facilities through several programs In our study, adolescents age 15-19 and young adults age 20-24 were less likely to be tested, for both genders.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Despite having lower levels of HIV knowledge, women's HIV testing rates are much higher than for men, at 62% versus 27%. This seems to be a constant finding across studies (9)(10)(11)20). It suggests that women have better access to health facilities through several programs In our study, adolescents age 15-19 and young adults age 20-24 were less likely to be tested, for both genders.…”
Section: Discussionmentioning
confidence: 60%
“…The use of urinary or saliva rapid HIV tests can be promoted as they are associated with HIV testing (28,29). However, a study conducted in the USA has shown that the optimal age for HIV testing adolescents and young adults is 25, and screening at age 18 or younger is a less efficient strategy (11). Another challenge could be consent for adolescents under age 18.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Neilan and coauthors provide model-based evidence against focusing routine one-time HIV screening among US youth younger than 18 years that supports the current practice of only 13% of adolescents <18 years being screened for HIV [6,7]. But current practice has been inadequate in addressing the HIV epidemic in youth in the US.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Adolescent Health, Neilan and coauthors report the findings from their model-based cost-effectiveness and clinical impact analysis to determine the optimal age (beginning at age 13 years) for routine one-time HIV screening among US adolescents and young adults without identified HIV risk factors [7]. The authors hypothesize that offering a onetime HIV screening test "too early" may cause harm by missing infections that occur later and speculate that resources used for HIV screening could detract from other health priorities throughout adolescence and young adulthood.…”
mentioning
confidence: 99%
“…In the literature, HIV test uptake was found associated with several individual factors, including age and gender-young people are less likely to seek HIV testing (7)(8)(9), while females are more likely to be tested (9)(10)(11). Another factor is person's sexual orientation and behavior (1, [12][13][14][15].…”
mentioning
confidence: 99%